Adlercreutzia-modulated polyunsaturated fatty acid metabolism underlies nicotine’s anti-obesity effects - Duan, Yifan; Li, Xiao; Chai, Ying; Chen, Huan; Hou, Hongwei (Frontiers in Microbiology, 2025)
BackgroundThe regulatory effects of nicotine on energy balance through central and peripheral mechanisms have been reported. However, its impact on obesity and gut microbiota at safe doses remains unclear.ResultsIn this study, it was found that chronic oral nicotine administration daily at relative low dose (0.5 mg/kg) significantly alleviated high-fat diet (HFD)-induced obesity phenotypes in mice, including body weight gain, fat deposits, hepatic steatosis, inflammation and metabolic dysfunction. Gut microbiota depletion and fecal microbiota transplantation (FMT) confirmed that these beneficial effects were microbiota-dependent. Metagenomic sequencing confirmed that nicotine administration reshaped gut microbiota composition, and specifically enriched the commensal genus Adlercreutzia, whose increased abundance correlated with improved biochemical indicators related to obesity. Furthermore, transplantation of Adlercreutzia reproduced anti-obesogenic effects, suggesting it was a key factor for nicotine reducing HFD-induced obesity. Untargeted metabolomics analysis combined association analysis further demonstrated that nicotine modulated host metabolic profiles via gut microbiota-metabolite axis, particularly enhancing Adlercreutzia-linked lipid metabolites involved in polyunsaturated fatty acid (PUFA) metabolism.ConclusionCollectively, our study elucidates the critical involvement of gut microbiota in nicotine-induced obesity amelioration, uncovers a novel Adlercreutzia-PUFA metabolic axis mediating nicotine’s anti-obesity effects, and highlight Adlercreutzia potentiation as a promising microbiota-directed invention strategy for obesity and metabolic syndrome.